Impact of room acoustics and visual cues on speech perception and talker localization by children with mild bilateral or unilateral hearing loss - Lewis, Dawna; Al-Salim, Sarah; McDermott, Tessa; Dergan, Andrew; McCreery, Ryan W. (Frontiers in Pediatrics, 2023)
Introduction. This study evaluated the ability of children (8-12 years) with mild bilateral or unilateral hearing loss (MBHL/UHL) listening unaided, or normal hearing (NH) to locate and understand talkers in varying auditory/visual acoustic environments. Potential differences across hearing status were examined.. Participants heard sentences presented by female talkers from five surrounding locations in varying acoustic environments. A localization-only task included two conditions (auditory only, visually guided auditory) in three acoustic environments (favorable, typical, poor). Participants were asked to locate each talker. A speech perception task included four conditions (auditory-only, visually guided auditory, audiovisual, auditory-only from 0 o azimuth [baseline]) in a single acoustic environment. Participants were asked to locate talkers, then repeat what was said.Results. In the localization-only task, participants were better able to locate talkers and looking times were shorter with visual guidance to talker location. Correct looking was poorest and looking times longest in the poor acoustic environment. There were no significant effects of hearing status/age. In the speech perception task, performance was highest in the audiovisual condition and was better in the visually guided and auditory-only conditions than in the baseline condition. Although audiovisual performance was best overall, children with MBHL or UHL performed more poorly than peers with NH. Better-ear pure-tone averages for children with MBHL had a greater effect on keyword understanding than did poorer-ear pure-tone averages for children with UHL.Although children could locate talkers more easily and quickly with visual information, finding locations alone did not improve speech perception. Best speech perception occurred in the audiovisual condition; however, poorer performance by children with MBHL or UHL suggested that being able to see talkers did not overcome reduced auditory access. Children with UHL exhibited better speech perception than children with MBHL, supporting benefits of NH in at least one ear.